GENERALIZED JORDAN HOMOMORPHISMS AND JORDAN TRIPLE HOMOMORPHISMS ONTO PRIME RINGS - Majeed, Abdul Rhman; Haheen, Rajaa (Iraqi Journal of Science, 2024)
In this paper we initiate the study of generalized Jordan homomorphism and generalized Jordan triple homomorphism onto prime rings.